Pyrolusite Bioleaching by an Indigenous Acidithiobacillus sp KL3 Isolated from an Indonesian Sulfurous River Sediment - Endah Retnaningrum; Wahyu Wilopo (Universitas Gadjah Mada, 2019)
The manganese bioleaching process of pyrolusite from Kliripan, Indonesia using Acidithiobacillus sp KL3 was investigated. The influence pulp densities of pyrolusite (0.01, 0.02, 0.03 and 0.05 g/cm3) on the bioleaching processes were studied for 16 days. The reduction on pH values, the increasing of oxidation-reduction potential (ORP), sulfate and manganese concentration were analyzed. The manganese bioleaching mechanism of pyrolusite by the strain was monitored using Scanning Electron Microscope-Energy Dispersive-X-ray Spectroscopy (SEM-EDX). The results indicated that 0.02 g/cm3 of pyrolusite was considered to be the optimal pulp density for manganese bioleaching process. During this process, pH values decreased, furthermore resulted in increasing of ORP, the concentration of sulfate and manganese. SEM-EDX analysis clearly showed the evidence of directly bacterial cell attachment into the surface of pyrolusite. Extracellular polymeric substances (EPSs) were further founded on that surface. Sulfur elemental was oxidized by the strain which was then confirmed of resulting in solubilized manganese.